Overcoming subjectivism in measuring the novelty of dissertation research as a problem of conventionality - A. N. Litvinenko; Yu. A. Lozina (Вестник университета)
The paper attempts to overcome subjectivism in the evaluation of dissertation research of the socio-humanitarian block, thus the positions of authors on this issue when measuring the identified scientific novelty are considered. The revealed contradictions that affect the subjective evaluation in the process of preparing and defending a dissertation are analysed. The author’s classification of novelty is proposed, having made possible to show its dependence on the amount of the studied sources. At present, the problem is not in determining the notion, but in determining what is already known. It is established that publication of “pure” and “local” author’s novelty contributes to its objective evaluation through procedures for protection of scientific works and defence of copyright. The current work substantiates the necessity to introduce a number of organisational and economic tools: video recording of the author’s speech at scientific conferences with the provisions to be defended for their comprehensive discussion; publication of draft conclusions on the dissertation of the Higher Attestation Commission’s expert council before its meeting; creation of an independent database of dissertation researches. It is concluded that the official publication of a scientific work as a civil-law me thod of its protection is an objective tool. It will help establish qualitative novelty in the dissertation and try to solve the problem of conventionality bet ween all interested subjects.